2018
DOI: 10.24247/ijmperdfeb201852
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Water Absorption Behaviour of Hardwickia Binata Fiber Reinforced Composites

Abstract: In recent years Natural fiber reinforced polymer composites have been used in the engineering applications.Composite materials possess high strength to weight ratio, and due to these facts composite materials are becoming popular among researchers and scientists. The major proportion of engineering materials consists of composite materials. Natural fiber reinforced green eco-friendly composites made from jute, hemp, sisal, banana, coir, green bagasse from the natural sources provide indisputable advantages ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…This study concludes that water absorption increases with increase in fiber content and it follows Fickian behavior; chemical resistance decreases with an increase in the fiber weight ratio and was maximum for 10 weight percentage of fiber. The chemical resistance test was conducted by a few researchers and observed their behavior and found that there was a weight gain for some acids and bases meanwhile there is some weight loss also observed for few [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This study concludes that water absorption increases with increase in fiber content and it follows Fickian behavior; chemical resistance decreases with an increase in the fiber weight ratio and was maximum for 10 weight percentage of fiber. The chemical resistance test was conducted by a few researchers and observed their behavior and found that there was a weight gain for some acids and bases meanwhile there is some weight loss also observed for few [20,21].…”
Section: Introductionmentioning
confidence: 99%